2023
DOI: 10.1134/s0021364023601173
|View full text |Cite
|
Sign up to set email alerts
|

On the Global Temperature of the Schwarzschild–de Sitter Spacetime

Abstract: It is shown that the Schwarzschild–de Sitter spacetime has the universal temperature. This temperature describes the thermal processes of decay of the composite particles and the other processes, which are energetically forbidden in the Minkowski spacetime, but are allowed in the de Sitter and in Schwarzschild–de Sitter backgrounds. In particular, this temperature describes the probability of ionization of the atom in the Schwarzschild–de Sitter, which is observed by the stationary observer at the point where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As distinct from the atom in flat space, the atom in the de Sitter vacuum has a certain probability of ionization. The rate of ionization is similar to the rate of ionization of an atom in flat spacetime in the presence of the thermal bath with temperature T = H/π [22][23][24][25][26]. In Section 2.2, it is shown that the same temperature determines the other activation processes that are energetically forbidden in Minkowski spacetime but allowed in the de Sitter background.…”
Section: Introductionmentioning
confidence: 89%
“…As distinct from the atom in flat space, the atom in the de Sitter vacuum has a certain probability of ionization. The rate of ionization is similar to the rate of ionization of an atom in flat spacetime in the presence of the thermal bath with temperature T = H/π [22][23][24][25][26]. In Section 2.2, it is shown that the same temperature determines the other activation processes that are energetically forbidden in Minkowski spacetime but allowed in the de Sitter background.…”
Section: Introductionmentioning
confidence: 89%